The impact of COVID-19 on the mental health of nurses working in the pandemic: a literature review (Research, Society and Development, 2021)
The aim of this study was to identify the main psychological impacts experienced by nursing professionals working on the front line of the COVID-19 pandemic, to report the most comprehensive symptoms and why they generate stress and describe coping strategies to better cope with the pandemic and avoid psychic illness. This is a systematic review of the literature. It is based on the injuries caused to the health of the worker in times of pandemic. The review showed how resulted, that human recourses are insufficient with high working hours, providing fear of being contaminated and contagion to other people, lack of team members, precariousness in the description of protocols, lack of adequate professional training, uncertainty of drug measures to control the disease, conditions unhealthy health services that may cause illness. Of these, the most cited were stress, anxiety, depression, insomnia, fear and posttraumatic stress, occupational stress, Burnout Syndrome, emotional exhaustion, anguish, and sleep disorders. We found that psychological support and better working conditions are essential for the nursing professional to exercise quality care continuously. In view of this situation, it is necessary to implement prevention measures to minimize the impacts on mental health of nurses active in the COVID-19 pandemic, which are: implantation adequate training through health institutions and encouraging integrative practices such as meditation, yoga, and similar activities to reduce stress, having adequate rest between working days with a good power supply.